Effect of renal function on serum concentration of 1,5-anhydroglucitol in type 2 diabetic patients in chronic kidney disease stages I-III: a comparative study with HbA1c and glycated albumin - Hasslacher, Christoph; Kulozik, Felix (Journal of diabetes, 2016)
Background 1,5-Anhydroglucitol (1,5-AG) is a new blood glucose control marker reflecting temporary glucose elevations. However, 1,5-AG is of limited value in patients with advanced renal insufficiency. The aim of the present study was to assess the correlation between 1,5-AG levels and renal function in patients with earlier stages of nephropathy compared with another two markers of diabetes control, namely HbA1c and glycated albumin (GA). Methods The following parameters were measured in 377 patients with type 2 diabetes: HbA1c, serum concentrations of 1,5-AG, GA and creatinine, hemoglobin, urinary albumin/creatinine ratio, and urinary excretion of α1-microglobulin (A1M). Estimated glomerular filtration rate (eGFR) was calculated according to the Cockgroft-Gault formula. Results There was a negative correlation between 1,5-AG and renal function (r = −0.18; P < 0.001). Concentrations of 1,5-AG were, on average, 27.2% lower in patients with glomerular hyperfiltration (eGFR >120 mL/min) compared with patients with moderate renal impairment (eGFR 30-59 mL/min; P = 0.016). In contrast, HbA1c, GA levels and urinary A1M excretion did not differ between the two patient groups. The mean age of patients with eGFR 30-59 mL/min was substantially higher than that of patients with glomerular hyperfiltration (P < 0.001). Thus, an age-related change in the renal glucose threshold could be the reason for the observed correlation between 1,5-AG and renal function. Conclusions In clinical practice, age and renal function must be taken into consideration when interpreting 1,5-AG levels, even in the absence of advanced renal impairment.
First published: 28 November 2015
Gesehen am 07.08.2019